KONTRIBUSI SENYUM PUSTAKAWAN MENINGKATKAN KUNJUNGAN PEMUSTAKA DI UPT PERPUSTAKAAN UNIVERSITAS BENGKULU - Elnadi, Isran; Widia Sari, Sevtika (UPT Perpustakaan Universitas Bengkulu, 2025)
This article discusses the contribution of librarian smiles in increasing user visits to the UPT Perpustakaan Universitas Bengkulu. The method used is a literature study. The material obtained through this literature study is collected, reviewed and then analyzed. Based on the results of studies that have been carried out, it was found that a librarian's smile can increase user visits. Judging from the data on visits from January 2023 to November 2024 as follows: visitors in January 2024 increased (1.4%), February 2024 there was an increase (3.6%), March 2024 increased (3.9%), April 2024 increased (3.6%), May 2024 there was an increase (3.6%), June 2024 there was an increase (8.6%), July 2024 increased (1.5), August increased (0.7%), September 2024 increased (0.5%), October 2024 there was an increase (0.5%), in November there was an increase (1.7%). Meanwhile, in December 2024 there were no visitors, because we conducted research at the end of November 2024. For more details on the increase in visits from January 2023 to November 2024, see table 1 on page 7, table 2 on page 8, and table 3 on page 9.